On the Evidence of a Dark Matter Density Spike around the Primary Black Hole in OJ 287 - Deb, Debabrata; Gopakumar, Achamveedu; Valtonen, Mauri J. (IOP Publishing Ltd, 2025)
The central engine of blazar OJ 287 is arguably the most notable supermassive black hole (SMBH) binary candidate that emits nanohertz (nHz) gravitational waves. This inference is mainly due to our ability to predict and successfully monitor certain quasiperiodic doubly peaked high brightness flares with a period of similar to 12 yr from this blazer. The use of post-Newtonian accurate SMBH binary orbital description that includes the effects of higher-order gravitational-wave emission turned out to be a crucial ingredient for accurately predicting the epochs of such Bremsstrahlung flares in our SMBH binary central engine description for OJ 287. It was very recently argued that one should include the effects of dynamical friction, induced by certain dark matter density spikes around the primary SMBH, to explain the observed decay of SMBH binary orbit in OJ 287. Invoking binary pulsar timing-based arguments, measurements, and OJ 287's orbital description, we show that observationally relevant SMBH binary orbital dynamics in OJ 287 are insensitive to dark-matter-induced dynamical friction effects. This implies that we could only provide an upper bound on the spike index parameter rather than obtaining an observationally derived value, as argued by M. H. Chan and C. M. Lee.